Dampak Pandemi Covid-19 terhadap Perubahan Sosial dalam Pendidikan - Resky Amalia (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2022)
This study aims to determine whether the Covid-19 pandemic has an impact on social changes in education, with the methods used, namely qualitative methods and types of field research, the research location was conducted at Halu Oleo University on January 25 - February 5, 2021. used in qualitative research is observation, interviews, while the data analysis used in this study is data analysis conclusion / verification.